Dataset on communal popular initiatives in Germany for the year 2018 - Premat, Christophe (Stockholm University, 2019)
The dataset is created for the year 2018 in Germany for 267 popular initiatives at the local level where the information was collected regarding the following variables: topic of initiative, State legislation, turnout, validity of the initiative, success of the popular initiative, proportion of yes voters in case of a referendum, size of municipality, profile of initiators (local council or citizens), proportion of no voters, index of mobilization, repartition index (difference between yes and no voters), approval rate, number of inhabitants, correction of initiative, status of the case (open/closed).

The dataset was created with the help of the existing popular initiatives registered by the University of Wuppertal and the association Mehr Demokratie in Germany.
The idea of the dataset is to evaluate in details on which factors the success of popular initiatives depend in the different German States (Länder). A repartition index (difference between yes and no voters) and a mobilization index (repartition index multiplied by the turnout) were calculated and added in the dataset. All the other variables were also created in order to balance the result of these initiatives.
The final aim is to be able to measure how direct democratic tools influence local politics in Germany. This is why it is important to examine the prevailing factors for the satisfaction of citizens who use these procedures.
In this dataset, the destiny of an initiative (failure/success) can be taken as the dependent variable and all the others could be classified as independent variables.Direct democracy offers possibilities for citizens to influence political decisions especially at the local level. In Germany, the local political systems have been affected by the introduction of direct democratic tools such as citizen initiatives and local referenda since the Reunification. The State legislations defined new conditions for citizen initiatives and municipal referenda with a minimum number of valid signatures for initiatives and a minimum approval rate for the referenda.
In the attached file, you will find the dataset in Excel file as well as a .dta file that you can open with the software Stata (https://www.stata.com/).
Keywords: Sociology not elsewhere classified; Political science not elsewhere classified; Political Science; Statsvetenskap; Sociology; Sociologi